Gerakan Penolakan Masyarakat Adat Terhadap Reklamasi Teluk Benoa - Hairiyah, Salma Maisyatul; Putri, Fadhilah Eka (Journal of Citizenship, 2024)
AbstractDecision to the reclamation of Benoa Bay which was based on human greed for nature invited a lot of rejection, especially from the Balinese people, plus there was a change in the status of Benoa Bay which was originally a conservation area in Presidential Decree No. 45 of 2011 became a cultivation area in Presidential Decree no. 51 of 2014. The movement of the Balinese people against the reclamation of Benoa Bay is colored by the thick collective identity of Balinese indigenous people. Initially, the reason for the movement against reclamation was dominated by reasons for the quality of life of the people and the health of the Balinese environment, but with the intervention of indigenous peoples, this movement has slowly shown a narrative of defending the sanctity of the Benoa Bay area. Writing this journal aims to examine the role of indigenous peoples in the movement against the Benoa Bay reclamation. The preparation of this journal uses a qualitative method of literature study approach. The result obtained is that the Balinese people formed a collective group of indigenous peoples who held an action. This action is based on the fact that reclamation is considered to be able to destroy various sacred points in Benoa Bay.Keywords: Benoa Bay reclamation, Indigenous peoples, Social movements.Â AbstrakKeputusan reklamasi teluk benoa yang berlandaskan keserakahan manusia terhadap alam mengundang banyak penolakan terutama dari masyarakat bali, ditambah lagi ada perubahan status teluk benoa yang semula adalah wilayah konservasi pada Perpres No. 45 Tahun 2011 menjadi kawasan budidaya pada Perpres No. 51 Tahun 2014. Gerakan masyarakat bali menolak reklamasi teluk benoa diwarnai dengan pekatnya identitas kolektif warga adat bali. Pada awalnya alasan gerakan penolakan reklamasi ini didominasi oleh alasan kualitas kehidupan masyarakat dan kesehatan lingkungan bali, namun atas campur tangan masyarakat adat perlahan gerakan ini memperlihatkan narasi pembelaan kesucian wilayah teluk benoa. Ditulisnya jurnal ini bertujuan untuk mengkaji peran masyarakat adat pada gerakan penolakan reklamasi teluk benoa. Penyusunan jurnal ini menggunakan metode kualitatif pendekatan studi literature. Hasil yang didapat ialah masyarakat bali membentuk kelompok kolektif masyarakat adat yang mengadakan aksi. Aksi tersebut didasari karena reklamasi dianggap dapat menghancurkan beragam titik suci yang ada di teluk benoa.Kata kunci: Reklamasi Teluk Benoa, Masyarakat adat, Gerakan sosial.